Aerodynamic Performance of a Dragonfly-Inspired Tandem Wing System for a Biomimetic Micro Air Vehicle - Salami, Erfan; Montazer, Elham; Ward, Thomas A; Nik Ghazali, Nik Nazri; Anjum Badruddin, Irfan (Frontiers in Bioengineering and Biotechnology, 2022)
The flying agility demonstrated by dragonflies is accomplished by means of complex aerodynamic forces produced by flapping their four wings arranged in a tandem configuration. The current article presents a novel tandem flapping wing mechanism that was used to experimentally investigate these aerodynamic forces. Such a mechanism could be used in a future biomimetic micro air vehicle (BMAV) design. The mechanism uses an electromagnetic actuator to flap the wings in a linear up-down stroke motion with a variable beat frequency (30 to 210 Hz) at various angles-of-attack (-10° to 20°). The results show that the tandem wings generate approximately 50% higher lift, compared with the forewing or hindwing pairs acting alone. The tandem wings also improve stability, which could potentially allow hovering.